NOTES ON THREE SPECIES OF PISON JURINE, 1808 (HYMENOPTERA: CRABRONIDAE) COLLECTED IN RIO CLARO (SP), BRAZIL - Pinto, N.p.o. [UNESP]; Fowler, H.g. [UNESP]; Digiampietri, E.a. [UNESP]; Gobbi, N. [UNESP] (Instituto Biológico, 2024)
The genus Pison Jurine (in Spinola), 1808 (Hymenoptera: Crabronidae) was revised by Menke, 1988 and three subgenera were placed in synonymy with Pison: Pisonoides F. Smith, 1858; Krombeiniellum Richards,1962 and Entomopison Menke, 1968a. The genus includes 42 native species in the Neotropical Region and more of the half of these are found in Brazil. Some of them make mud nests on diverse substrates, such as: on the underface of broad leafs, on the wall of human constructions, boxes, windows, and in the edges of roofs. The coccons of some of these species are closed cells with a fine layer of mud in a small abandoned nest (made on vegetable fibres) of Mischocyttarus de Saussure, 1853 sp. (Hymenoptera.: Vespoidea, Vespidae, Polistinae, Mischocyttarini). This is the first record of nesting behavior for this species. Male of P. duckei is still undescribed. The third specie observed was P. delicatum Menke, n sp.

O gênero Pison Jurine (in Spinola), 1808 (Hymenoptera: Crabronidae) foi revisado por Menke, 1988 e três subgêneros foram colocados em sinonímia com Pison: Pisonoides F. Smith, 1858; Krombeiniellum Richards, 1962 e Entomopison Menke, 1968a. O gênero contém 42 espécies nativas na Região Neotropical e mais da metade dessas espécies são encontradas no Brasil. Algumas delas constróem ninhos de barro em diferentes substratos: na face inferior de largas folhas, em paredes de alvenaria, caixas, janelas, beirais de telhado. Os casulos de algumas dessas espécies são constituídos de minúsculos grãos de areia perfeitamente encaixados e fixados pela larva da vespa antes de empupar, como os observados em P. aureofaciale Strand,1910. Foram encontrados exemplares de P. duckei Menke,1968b, um macho e uma fêmea, em células fechadas com fina camada de barro em pequeno ninho abandonado (feito de fibras vegetais) de Mischocyttarus de Saussure, 1853 sp. (Hymenoptera : Vespoidea, Vespidae, Polistinae, Mischocyttarini) sendo este o primeiro relato do hábito de nidificação e descrição do casulo para a espécie. Macho desta espécie ainda não foi descrito. A terceira espécie observada foi de P. delicatum, Menke, n.sp.
Keywords: Hymenoptera; Crabronidae; Pison duckei; Paureofaciale P; delicatum,; behavior.; Hymenoptera; Crabronidae; Pison duckei; Paureofaciale; P; delicatum, comportamento